Effect of Gibberellic Acid on Morphological and Floral Traits, Outcrossing, Seed Yield and Quality in Parental Lines of Hybrid Rice and Efficacy of Ultra Low Volume Sprayer in Economisation of Dose of Gibberellic Acid - SUDIPTA BASU,; H.A.KHAN,; ILYAS AHMED, (Seed Research, 2026)
An investigation was undertaken with two CMS lines, IR58025A and IR62829A with their respective maintainers in split plot design to determine the optimum dose and stage of application of gibberellic acid (GA) in parental line seed multiplication plot of hybrid rice. In addition, effect of GA, on morphological and floral traits, outcrossing percentage, seed yield and quality with efficacy of ultra low volume (ULV) sprayer in economisation of dose of above chemical was also evaluated. Spraying was done @30, 60, 90, 120 and 150g/ha with knapsack sprayer (KS) and @ 30, 45, 60 and 75g/ha with ULV sprayer at late boot leaf, five per cent panicle exsertion and flowering stage. Results of the study indicated that application of GA, @ 120 and 150g/ha with KS and @ 60 and 75g/ha with ULV sprayer were superior and spraying at five per cent panicle exsertion and flowering gave better results than application at late boot leaf stage. There was significant enhancement in plant height, panicle exsertion, floral traits i.e. duration and angle of spikelet opening, stigma exsertion, outcrossing percentage and seed yield with increment of GA, dose but had no effect on 100 seed weight and seed quality. The correlation studies indicated that the angle and duration of spikelet opening and outcrossing percentage were the main factors in enhancing the seed yield. The results showed that the yield realized per rupee investment on GA, reduced at higher doses. The study highlighted the efficacy of ULV sprayer in economisation of the dose. Although, GA, has established its inevitability in hybrid rice seed production but the study emphasized the need of its judicious and timely application at optimum dose for economizing the seed production.